The Effect of Sandblasting on Bond Strength of Soft Liners to Denture Base Resins: A Systematic Review and Meta-Analysis of In Vitro Studies - Fahimeh Hamedirad; Marzieh Alikhasi; Mahya Hasanzade (Hindawi Limited, 2021)
Objectives. This study aimed to evaluate the effect of sandblasting on the bond strength of denture base resin to soft liners. Materials and Methods. This report follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. PubMed, Embase, Cochrane, Scopus, and OpenGrey databases were searched for in vitro studies that compared sandblasting with no treatment in terms of the tensile, shear, and peel bond strength of resilient lining materials (acrylic-based or silicone-based) to polymethyl methacrylate denture base resin. Based on the outcome, the analysis was carried out in three groups of tensile, shear, and peel bond strength. Subgroup analysis was done for the effect of size of particles on sandblasting, blasting pressure, and type of soft liner whenever possible. Heterogeneity was evaluated among the studies, and meta-analysis was performed with random effect models (p<.05). Results. After screening, 16 articles met the inclusion criteria for meta-analyses. No treatment showed significantly higher tensile (p<0.001) or peel (p=0.04) bond strength, although shear bond strength of sandblasted resin was significantly better (p=0.008). Results of subgroup analyses of particle size favored the control group in 50 µ Al2O3 particle size (p<0.001). In analyses of blasting pressure, the control group had significantly better tensile bond strength than specimens with blasting pressure ≤1 bar (p<0.001) while specimens with blasting pressure beyond 1 bar showed significantly more tensile strength than control group (p=0.03). In silicon-based liners, groups without any surface treatment had significantly higher tensile bond strength (p<0.001). Conclusion. According to the in vitro studies, sandblasting would not lead to significant increase in bond strength of soft liner to the denture base resin.